KONTRIBUSI IISMA TERHADAP PENGEMBANGAN KETERLAMPILAN KEWIRAUSAHAAAN MAHASISWA INDONESIA - Kiwi Hartono, Nelly (Puslitabmas Batam Tourism Polytecnic, 2025)
This research explores the contribution of the IISMA program in enhancing entrepreneurial skills among Indonesian students. The study aims to investigate how the program promotes entrepreneurial mindsets, innovation, and leadership in a global business environment. A descriptive qualitative approach was used, with data collected through interviews, observations, and document analysis. The findings reveal that IISMA significantly influences the development of creativity, risk-taking, and practical innovation skills among participants. Additionally, the program strengthens students' adaptability, collaboration, and leadership capabilities, preparing them to face future global economic challenges. In conclusion, the IISMA program plays a vital role in equipping Indonesian students with the necessary skills to thrive in a competitive global business landscape.